Case Report: Totally Laparoscopic Resection of Retroperitoneal Paraganglioma Masquerading as a Duodenal Gastrointestinal Stromal Tumor - Zhang, Zhi; Tu, Zhengbin; Lv, Zhiqiang; Luo, Yang; Yuan, Jianmao (Frontiers in Surgery, 2021)
Abstract Introduction: Retroperitoneal paraganglioma (RPGL) is a rare clinical tumor derived from the retroperitoneal sympathetic paraganglion tissue. Since RPGLs are locate deeply and have no specific symptoms and imaging manifestations at the early stage, which easily causes missed diagnosis or misdiagnosis. In addition, reports on totally laparoscopic resection of RPGLs are scarce due to their close proximity to large vessels, giant size, uncertain location and unknown malignant status. Case presentation: We present here the case of totally laparoscopic resection of a 6.4cm×5.4cm RPGL that was discovered during a workup for discomfort and upper abdominal pain in a 68-year-old female patient, mimicking a gastrointestinal stromal tumor (GIST) of the duodenum, Which was confirmed as a RPGL based on the histopathological and immunohistochemical findings. Conclusions: RPGL is a rare tumor, and the transperitoneal laparoscopic approach for the RPGL is a safe, applicable method with less trauma and quick recovery, which is worth clinical popularizing and application. Moreover, the survival prognosis of RPGL patients are related to metastasis, and lifelong follow-up should be emphasized.